Uniform traffic patterns using virtual cut-through flow control on VMMN - Yahya Hag, Ala Ahmed; Rahman, M.M. Hafizur; Mohd. Nor, Rizal; Sembok, Tengku Mohd; Miura, Yasuyuki; Inoguchi, Yasushi (Elsevier Ltd., 2015)
The previous study of static network performance of a Vertical Midimew connected Mesh Network (VMMN) was shown to be good. However, its dynamic communication performance has not been evaluated yet, we have proposed a deadlock free dimension order routing algorithm using 4 virtual channels. In this paper, The TOPAZ simulator is used to evaluate the dynamic communication performance of a VMMN with virtual cut-through flow control under uniform traffic pattern. We found that the VMMN dynamic communication performance is better than that of the hierarchical TESH network and its counter rival MMN.